Learn from international recommendations and experiences of countries that have successfully implemented monoclonal antibody prophylaxis for prevention of RSV infection - Sara Manti; Eugenio Baraldi (Italian Journal of Pediatrics)
Abstract Respiratory syncytial virus (RSV)-mediated bronchiolitis causes a significant global health burden. Despite this, for several years, the only approved agent for RSV prophylaxis was the anti-RSV monoclonal antibody Palivizumab, reserved for a small population of infants at high risk of developing severe RSV disease. Recently, the availability and approval of nirsevimab to immunize all infants against RSV infection since their first RSV season represented a crucial paradigm shift in RSV prevention. Nirsevimab has been shown to be safe and effective (> 80%) against RSV lower respiratory tract infections (LRTIs) in all infants and children at their first season of RSV. Surveillance studies have demonstrated 90% effectiveness in reducing all-cause hospitalizations, all-cause LRTI hospitalizations, RSV-related LRTI hospitalizations, and severe RSV-related LRTIs. Moreover, the consistency and reproducibility of the beneficial outcomes coming from the prophylaxis with nirsevimab highlights its potential to deliver substantial health benefits, positioning monoclonal antibody administration as a cornerstone in the fight against RSV-related morbidity and mortality. Implementing immunization strategies for infants and children is crucial to align the international experiences and guarantee universal protection. This review provided an updated overview of the monoclonal antibody strategy for preventing RSV infection.